Pasar Seni Kerajinan Rotan Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer - Vera Yunita; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Rumbai district in Pekanbaru city is an area the community as a woven craft area, most of the people earn a living as rattan and wood craftsmen. Rattan craft industry is one business activities that has existed for a long time in Pekanbaru city which has a high selling value. But now, rattan craft industry is currently less developed, therefore efforts are needed to realize effective product marketing. Less of management of rattan craft is the background of the rattan crafts art market design. Art market serves as a place to support the creativity of rattan craftsmen and access to make it easier for consumers to get rattan craft. The design method used is primary data containing documentation and secondary data from of literature and comparative studies. The rattan craft market applies with contemporary architecture, contemporary architecture display different design in the rattan craft market building. The concept applied in design of rattan craft market is “Woven”. The concept of woven is inspired by the function of this market. The design is expected to be able to accommodate the activities of producers and consumers of rattan craft.Keywords: Rattan Craft, Contemporary Architecture